Characterization of the immune response in subcutaneous chambers of guinea pigs immunized with a ribosomal preparation from Neisseria gonorrhoeae. - Wannemuehler, M J (1982)
Immunization of guinea pigs with ribosomal preparations has been previously shown to be protective against chamber infection with Neisseria gonorrhoeae, and this protection could be correlated with the presence of serum bactericidal antibody. Analysis of the chamber fluids from ribosome-immunized and nonimmunized guinea pigs has demonstrated that the chamber fluid may accurately reflect serum antibody levels and proteins. At least one major population of antiribosomal antibodies is present in both immune serum and chamber fluid as revealed by lines of identity between these components. Antibody- and complement-mediated bactericidal assays revealed that matched chamber fluids and sera from immune animals had comparable bactericidal titers. These results suggest that the antibody-complement-mediated bactericidal activity plays a major role in the protection against N. gonorrhoeae infection. Protection could not be explained on the basis of the cellular components of the inflammatory response since both immune and nonimmune chambers had comparable increases in polymorphonuclear neutrophils, monocytes, and lymphocytes after challenge.